2006
DOI: 10.1007/s00216-006-0816-4
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared reflectance spectroscopy as a fast and non-destructive tool to predict foliar organic constituents of several woody species

Abstract: Near-infrared reflectance spectroscopy (NIRS) was used to estimate N, neutral detergent fibre (NDF), acid detergent fibre (ADF), lignin and cellulose contents in leaves of a heterogeneous group of 17 woody species from the Central Western region of the Iberian Peninsula. The sample set consisted of 182 samples of leaves of deciduous and evergreen species, showing a wide range of concentrations determined by reference methods: 6.60-35.2 g kg-1 (N), 15.5-66.0% (NDF), 10.2-57.3% (ADF), 3.45-27.4% (lignin) and 5.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 36 publications
3
35
2
Order By: Relevance
“…Recently, spectroscopic data combined with PLSR modelling has been used to estimate levels of various other leaf biochemical and nutritional constituents (Gillon et al , 1999; Richardson and Reeves, 2005; Petisco et al , 2006). For example, Asner and Martin (2008) found that spectroscopy could be used to estimate leaf concentrations of chlorophylls (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, spectroscopic data combined with PLSR modelling has been used to estimate levels of various other leaf biochemical and nutritional constituents (Gillon et al , 1999; Richardson and Reeves, 2005; Petisco et al , 2006). For example, Asner and Martin (2008) found that spectroscopy could be used to estimate leaf concentrations of chlorophylls (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, target foliar traits have included concentrations of nitrogen ( N mass , Bolster et al , 1996; Gillon et al , 1999), lignin, cellulose (Wessman et al , 1988 a ; Martin and Aber, 1997; Kokaly and Clark, 1999; Petisco et al , 2006), and photosynthetic pigments (Richardson et al , 2002; Gitelson et al , 2003; Moorthy et al , 2008) as well as water content (Sims and Gamon, 2003; Stimson et al , 2005; Cheng et al , 2008). In addition, leaf isotopic ratios (δ 13 C and δ 15 N; Richardson and Reeves, 2005; Wang et al , 2007; Kleinebecker et al , 2009), specific leaf area (SLA; Asner and Martin, 2008), and leaf mass per area (LMA; Asner et al , 2011; Doughty et al , 2011) have been successfully estimated using leaf optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral reflectance values of each sample were transformed into pseudo-absorption values; that is, log [1/R]) where R is reflectance (see Bolster et al, 1996;Gillon et al, 1999;Richardson and Reeves III, 2005;Petisco et al, 2006;Kleinebecker et al, 2009). There is strong autocorrelation in pseudo-absorption values, so PLSR involves dimensionality reduction, producing orthogonal uncorrelated latent vectors containing the maximum explanatory power in relation to the trait data (Wold et al, 2001).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…To test and select a truly robust NIRS model, a large and diverse external independent validation sample set is necessary (Martens and Dardenne 1998;Petisco et al 2006;Richardson and Reeves 2005). In this study, 132 sample spectra were set aside as external, independent validation set, which was not included in either of the calibration and test validation, but contained, at least in part, some of the original pure root material.…”
Section: Model Development and Validationmentioning
confidence: 99%